Late presentation with HIV in Africa: phenotypes, risk and risk stratification in the REALITY trial - Siika, A; McCabe, L; Bwakura-Dangarembizi, M; Kityo, C; Mallewa, J; Berkley, J; Maitland, K; Griffiths, A; Baleeta, K; Mudzingwa, S; Abach, J; Nathoo, K; et al. (Oxford University Press, 2018)
Background In sub-Saharan Africa, severely immunocompromized HIV-infected individuals have high mortality shortly after starting antiretroviral therapy (ART). We investigated predictors of early mortality and “late presenter” phenotypes. Methods ART-naïve adults and children ≥5 years with CD4<100 cells/mm3 initiating ART in Uganda, Zimbabwe, Malawi and Kenya were enrolled in the REALITY trial (ISRCTN43622374). Baseline predictors of mortality through 48 weeks on ART were identified using Cox regression with backwards elimination (exit p>0.1), and late presenter phenotypes using hierarchical clustering. Results Final multivariable models included 1711 participants (26 <13 years) of whom 203(12%) died. Mortality was independently higher with older age; lower CD4, albumin, haemoglobin, grip strength; presence of WHO stage 3/4 weight-loss, fever, vomiting; and problems with mobility or self-care at baseline (all p<0.04). Receiving enhanced-prophylaxis independently reduced mortality (p=0.02). Five “late presenter” groups were identified. Group-1 (N=355), with highest mortality (25%; median CD4 28 cells/mm3), had high symptom burden, weight loss, poor mobility and low albumin and haemoglobin. Group-2 (N=394; 11% mortality; 43 cells/mm3) also had weight loss, with high white cell, platelet and neutrophil counts suggesting underlying inflammation/infection. Group-3 (N=218; 10% mortality) had similar CD4 (27 cells/mm3) to Group-1, but low symptom burden and maintained fat mass. The remaining two groups (N=218, N=398) had few symptoms, median CD4 42-48 cells/mm3 and lower (4-6%) mortality. Conclusions Clinical and laboratory features characterized groups with highest mortality following ART initiation. A screening tool appropriate to facility level could identify patients with low CD4 counts for prioritising same-day ART initiation, enhanced prophylaxis and more intensive follow-up.